Diagnostic Accuracy and Cost Savings Associated with Dermoscopy: An Economic Study - Shir-az, Ofir; Yaacobi, Dafna Shilo; Berl, Ariel; Yosefof, Eyal; Grush, Andrew E.; Shalom, Avshalom (Seminars in Plastic Surgery, 2022)
Cutaneous malignancies are the most common overall cancer worldwide. Dermoscopy is widely used among various specialties to evaluate skin lesions and to differentiate benign from malignant lesions. Our objective was to evaluate the diagnostic capability and the economic impact of dermoscopy. The accuracy of diagnoses and economic costs of treating skin lesions were compared between two periods: 2001 to 2007 (prior the use of dermoscopy) and 2009 to 2011 (following implementation of dermoscopy). During the earlier period, 6,549 skin lesions were excised, of which 1,042 (15.9%) were malignant. During the later period, 2,578 lesions were excised, of which 610 (23.7%) were malignant. The potential savings estimated for the Israeli health care system are 6,500,000 USD. The use of dermoscopy increases sensitivity in diagnosing malignant skin lesions, enables diagnoses at an earlier stage, and has the potential for major cost savings for the health care system.
Keywords: dermoscopy; basal cell carcinoma; squamous cell carcinoma; melanoma; health care system; economic impact